2009
DOI: 10.3727/096504010x12704916124747
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of a Novel 2-Arylidene-4,7-dimethyl indan-1-one Against Human Breast Adenocarcinoma Cell Line by G<SUB>2</SUB>/M Cell Cycle Arrest

Abstract: A novel compound 2-arylidene-4,7-dimethyl indan-1-one synthesized was screened for anticancer effect against the human breast adenocarcinoma cell line, MCF-7. An IC50 value of > or = 80 microM, nontoxic to the normal breast cell line HBL-100, showed complete inhibition of the MCF-7 cells. Analysis of mechanisms showed nuclear fragmentation and DNA laddering in gel electrophoresis. GSH and GR levels were found to be reduced after the compound treatment. Cell cycle analysis using fluorescent cytometry revealed G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Our results were in agreement and another way of confirming the induction of apoptosis by MLT-401. It is well established from the literature [37] and our own previous investigations [17, 21] have shown that the cells which get accumulated in the M4 fraction were apoptotic cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our results were in agreement and another way of confirming the induction of apoptosis by MLT-401. It is well established from the literature [37] and our own previous investigations [17, 21] have shown that the cells which get accumulated in the M4 fraction were apoptotic cells.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have assessed various other arylidene derivatives exhibiting antibacterial [23], antifungal [24], or anticancer [25, 26] activities. Other members of our study group have also reported anti-cancer properties [17, 21] for a few derivatives of this family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure of FXY-1 (IUPAC-2-arylidene-4, 7-dimethyl indan-1-one) is shown in Figure 1b. FXY-1 was proven against breast adenocarcinoma cells and lung cancer cells (Prasanna & Harish, 2010). FXY-1 was reported to induce apoptosis in human lung carcinoma cells through inhibiting AKT-mitochondrial pathway (Rajagopalan et al, 2016).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Arylidene, with potential antitumor properties, belongs to this class of drug. We previously reported that an arylidene derivative (FXY-1) was effective against breast and lung cancer cells [8,9]. Based on these observations, we synthesized structural analogs of this compound by rational drug design and docked them with Akt to check the enzyme-compound affinity.…”
Section: Introductionmentioning
confidence: 99%